MEDIA PEMBELAJARAN BERBASIS PERTANIAN INDUSTRIAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI KEGIATAN EKONOMI - Widyawat, Wike; Sulthon, Ilma Kamila; Sudarti, Sudarti; Wuryaningrum, Rusdhiyanti (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Science learning has an important role in equipping students to be more sensitive to the social problems around them. Students' critical thinking needs to emerge inlearning so that they are able to see things from various sides. This research aims to develop audiovisual-based learning media in the form of agricultural industry-based learning videos on IPAS material, namely "buying and selling activities as a means of fulfilling needs," which is interesting and effective in improving the critical thinking skills of class IV students at SDNU Padomasan Jombang, Jember. This research method is development research, which in its application goes through several stages, namely: potential and problems, data collection, product design, design validation, design revision, product trials, use trials, and mass production. The critical thinking indicators referred to are providing simple explanations, building basic skills, concluding, providing further explanations, and developing strategies and tactics. Critical thinking indicators created in each learning activity can be used to develop students' critical thinking by placing agricultural industry products close to the environment and students' lives. Validation of audio-visual learning media is carried out by validators to assess it in terms of material content, media design, and language. The results of the research show that the feasibility has an average of 93.2% from the language aspect, 91.1% from the material aspect, and 95% from the media presentation aspect. These values indicate that audio-visual media is categorized as very feasible.